Isolation and biological characterization of Batx-I, a weak hemorrhagic and fibrinogenolytic PI metalloproteinase from Colombian Bothrops atrox venom - Patiño Llano, Arley Camilo (2010)
A hemorrhagic metalloproteinase, named Batx-I, was isolated from the venom of Bothrops atrox specimens (from Southeastern Colombian region) by a combination of CM-Sephadex C25 ion-exchange and Affi-gel Blue affinity chromatographies. This enzyme accounts for about 45% of venom proteins, and it has an ESI-MS isotope-averaged molecular mass of 23296.2 Da and a blocked N-terminus. Two internal fragments sequenced by mass spec trometric analysis showed similarity to other SVMPs from Bothrops venoms. To investigate the possible participation of Batx-I in the envenomation pathophysiology, proteolytic, f ibrinogenolytic, hemorrhagic, and other biological activities were evaluated. The minimal hemorrhagic dose obtained was 17 mg/20 g body weight. The enzyme showed proteolytic activity on azocasein, comparable with activity of BaP1. This activity was inhibited by EDTA and 1, 10 o-phenanthroline but not by aprotinin, pepstatin A or PMSF. Fibrinogenolytic activity was analyzed by SDS-PAGE, revealing a preference for degrading the Aa- and Bb-chains, although partial degradation of the g-chain was also detected. The protein lacks coagulant and defibrinating activity. The CK levels obtained, clearly reflects a myotoxic activity induced by Batx-I. The hemorrhagic and fibrinogenolytic activities exhibited by the isolated PI-SVMP may play a role in the hemorrhagic and blood-clotting disorders observed in patients bitten by B. atrox in Colombia.